(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This research delves into the overarching impact of state financial policies, particularly tax policies, on economic development spanning the years 2010 to 2022. The study explores the intricate relationship between these policies and social responsibility. The researchers meticulously trace pivotal stages and influential factors in shaping public policy, addressing challenges encountered by the government from 2003 to the present. The examination focuses on key facets of the state’s tax policy, emphasizing its role in expanding economic horizons. Social responsibility is assessed through four dimensions: economic responsibility, legal responsibility, ethical responsibility and charitable responsibility. To gauge these dimensions, a comprehensive questionnaire consisting of 32 items underwent thorough arbitration and evaluation, demonstrating commendable reliability through the alpha coefficient. Utilizing the statistical analysis program SPSS, the researchers analyzed the data, extracting descriptive statistical measures to elucidate the relationship and impact between tax policy and social responsibility dimensions. The study yields several noteworthy conclusions, highlighting the pivotal role of social awareness in fostering economic development. The improvement of living standards plays a crucial role in instigating social responsibility, and the meticulous automation of tax procedures can serve as a significant motivator for individuals to act with heightened social responsibility, thereby enhancing the efficiency of tax policy.